2008
DOI: 10.1097/brs.0b013e318188adfc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reliability of Post-Tetanic Motor-Evoked Potential Monitoring During Spinal Surgery Under General Anesthesia

Abstract: The results indicate that p-MEP is a more reliable method to detect changes in motor function during spinal surgery under general anesthesia in comparison with c-MEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Recently, we developed a new technique to improve the reliability of MEP recording, called post-tetanic MEP (p-MEP), in which the MEP amplitude, compared with that of conventional MEP (c-MEP), can be enlarged by tetanic stimulation of peripheral nerves prior to transcranial electrical stimulation [14][15][16][17]. Our previous data suggested that tetanic stimulation (50 Hz, 50 mA) of peripheral nerve with a duration of 3-5 s and a posttetanic interval of 1-5 s could be applied for the purpose of augmenting the MEP amplitude [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed a new technique to improve the reliability of MEP recording, called post-tetanic MEP (p-MEP), in which the MEP amplitude, compared with that of conventional MEP (c-MEP), can be enlarged by tetanic stimulation of peripheral nerves prior to transcranial electrical stimulation [14][15][16][17]. Our previous data suggested that tetanic stimulation (50 Hz, 50 mA) of peripheral nerve with a duration of 3-5 s and a posttetanic interval of 1-5 s could be applied for the purpose of augmenting the MEP amplitude [14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, falsepositive results of intraoperative MEPs have been reported repeatedly, at a range of 0% to 27%, because of the suppressive effects exerted by a variety of factors, including anesthetic agents, neuromuscular blocking agents, hemodynamic changes, temperature, and failure of electrodes [15,16]. In our series of 80 patients undergoing spine and spinal cord surgery, the false-positive rate of MEP monitoring was 4% when c-MEP was used for monitoring; however, when p-MEP was used for monitoring, the false-positive rate was 0% [14]. This study also showed that there were no false-negative results of c-MEP and p-MEP.…”
Section: Reliability Of P-mep Monitoringmentioning
confidence: 52%
“…Recent reports have indicated that the success rates of baseline MEP recording during spinal surgery were 89%-100% and 30%-50% in patients without and with preoperative motor weakness, respectively [12,13]. In our recent study, the success rates of baseline MEP recording were signifi cantly improved by using p-MEP in patients without and with preoperative motor weakness (c-MEP, 74.5% and 51.7%, respectively; p-MEP, 96.1% and 86.2%, respectively) [14].…”
Section: Reliability Of P-mep Monitoringmentioning
confidence: 92%
“…Generally the stimulus intensity of transcranial stimulation in spine and aortic surgery is determined at the beginning of MEP recording and is set just supramaximal to each stimulus (approximately 500 V). 1) In this study, the intensity of stimulus was 210 ± 37.6 V (range 140-250 V). Initially we identified the threshold level, at which the MEP waveform was elicited from only the contralateral APB.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, transcranial MEP can be performed without insertion of grid electrodes on the brain surface and throughout the course of surgery, and is therefore widely used not only in brain surgery but also in spine and aortic surgery. 1,5) Direct recording of MEPs from the spinal cord (D waves) after transcranial stimulation demonstrated that high-intensity stimulation can activate the corticospinal tract as deep as the pyramidal decussation. 3) To compensate for the weaknesses of direct MEP, we have used transcranial electrical stimulation combined with direct cortical stimulation to elicit MEPs for intraoperative monitoring.…”
Section: Introductionmentioning
confidence: 99%